Marxist and Christian Dialectics Of Liberation - S Kappen (Journal of Dharma, 1977)
In comparing Marxism and Christianity, it is necessary to keep in mind that their axes lie on different planes. Marxism is at once a philosophy, a sociology, a methodology of knowing and act- ing, and an economic theory. Christianity, on the contrary, is neither a philosophy, nor a sociology, nor a methodology, nor a theory of economics. The prime concern of Jesus was the absolute meaning and value of life, the ultimate ground and goal of human existence. He was concerned with the concrete problems of this world only insofar as God and his reign had a stake in them.